Engineering bioinspired bacteria-adhesive clay nanoparticles with a membrane-disruptive property for the treatment of Helicobacter pylori infection. Issue 36 (7th September 2016) - Ping, Yuan; Hu, Xiurong; Yao, Qi; Hu, Qida; Amini, Shahrouz; Miserez, Ali; Tang, Guping
Abstract : A bioinspired design strategy was exploited for engineering bacteria-targeting and membrane-disruptive nanoparticles for the effective antibiotic therapy of Helicobacter pylori infection. Abstract : We present a bioinspired design strategy to engineer bacteria-targeting and membrane-disruptive nanoparticles for the effective antibiotic therapy of Helicobacter pylori ( H. pylori ) infection. Antibacterial nanoparticles were self-assembled from highly exfoliated montmorillonite (eMMT) and cationic linear polyethyleneimine (lPEI) via electrostatic interactions. eMMT functions as a bioinspired 'sticky' building block for anchoring antibacterial nanoparticles onto the bacterial cell surface via bacteria-secreted extracellular polymeric substances (EPS), whereas membrane-disruptive lPEI is able to efficiently lyse the bacterial outer membrane to allow topical transmembrane delivery of antibiotics into the intracellular cytoplasm. As a result, eMMT-lPEI nanoparticles intercalated with the antibiotic metronidazole (MTZ) not only efficiently target bacteria via EPS-mediated adhesion and kill bacteria in vitro, but also can effectively remain in the stomach where H. pylori reside, thereby serving as an efficient drug carrier for the direct on-site release of MTZ into the bacterial cytoplasm. Importantly, MTZ-intercalated eMMT-lPEI nanoparticles were able to efficiently eradicate H. pylori in vivo and to significantly improve H. pylori -associated gastric ulcers and the inflammatory response in a mouse model, and also showed superior therapeutic efficacy as compared to standard triple therapy. Our findings reveal that bacterial adhesion plays a critical role in promoting efficient antimicrobial delivery and also represent an original bioinspired targeting strategy via specific EPS-mediated adsorption. The bacteria-adhesive eMMT-lPEI nanoparticles with membrane-disruptive ability may constitute a promising drug carrier system for the efficacious targeted delivery of antibiotics in the treatment of bacterial infections.